Diagnostic value of contrast-enhanced mag-netic resonance angiography in large-vessel vasculitis - Adler, Sabine; Sprecher, Marco; Wermelinger, Felix; Klink, Thorsten; Bonel, Harald M.; Villiger, Peter M. (Swiss Medical Weekly, 2017)
Objective: To evaluate contrast-enhanced magnetic resonance angiography (MRA) in diagnosis of in-flammatory aortic involvement in patients with clinical suspicion of large-vessel vasculitis. Patients and Methods: Seventy-five patients, mean age 62 years (range 16-82 years), 44 female and 31 male, underwent gadolinium-enhanced MRA and were evaluated retrospectively. Thoracic MRA was performed in 32 patients, abdominal MRA in 7 pa-tients and both thoracic and abdominal MRA in 36 patients. Temporal arterial biopsies were obtained from 22/75 patients. MRA positivity was defined as increased aortic wall signal in late gadolinium-enhanced axial turbo inversion recovery magnitude (TIRM) series. The influence of prior glucocorticoid intake on MRA outcome was evaluated. Results: MRA was positive in 24/75 patients, with lesions located in the thorax in 7 patients, the abdo-men in 5 and in both thorax and abdomen in 12. Prob-ability for positive MRA after glucocorticoid intake for more than 5 days before MRA was reduced by 89.3%. Histology was negative in 3/10 MRA-positive patients and positive in 5/12 MRA-negative patients. All 5/12 histology positive / MRA-negative patients had gluco-corticoids for 7gt;5 days prior to MRA and were diag-nosed as having vasculitis. Positive predictive value for MRA was 92%, negative predictive value was 88%. Conclusions: Contrast-enhanced MRA reliably identifies large vessel vasculitis. Vasculitic signals in MRA are very sensitive to glucocorticoids, suggesting that MRA should be done before glucocorticoid treat-ment.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Diagnostic imaging; Glucocorticoids; Magnetic resonance angiography; Predictive value of tests; Systemic vasculitis